Dissecting copper homeostasis in diabetes mellitus. Issue 4 (9th March 2017) - Lowe, Jennifer; Taveira‐da‐Silva, Rosilane; Hilário‐Souza, Elaine
Abstract: Diabetes Mellitus (DM) is characterized by elevated blood glucose levels (hyperglycemia). It can occur due to impaired secretion or action of the hormone insulin, which is produced by pancreatic beta‐cells to promote the entry of glucose into the cells. It is known that hyperglycemia has an important role in the production of reactive oxygen species in all types of DM and that an imbalance of transition metal as Cu and Fe plays a pivotal role in stimulating the oxidative stress. Different levels of some transition metals, as Cu, Fe, Mn, and Zn has been reported comparing diabetic animal models with the control group. An increased Cu status is also described in diabetic patients. Homeostasis of Cu depends on distinct proteins, where Cu(I)‐ATPases are important transmembrane proteins for acquisition, active transport, distribution and elimination of Cu ions. In this review we first provide an overview of the literature about the relationship between diabetes and copper, the modulation of Cu(I)‐ATPases activity and protein expression in DM, to next discuss the alternative treatments for diabetes using Cu chelation. © 2016 IUBMB Life, 69(4):255–262, 2017